Reliability and validity of the Basic Depression Questionnaire - Guillot-Valdés, María (Int J Clin Health Psychol, 2019)
Depressive disorders have a high prevalence around the world. They present a great comorbidity with other disorders like anxiety, thereby making a differential diagnosis very difficult. The Basic Depression Questionnaire was designed to palliate this issue by isolating specific depression symptoms. Our aim is to study the reliability, factorial structure, and differential item functioning of this questionnaire. Method: The sample consisted of 1,397 adults without psychological problems (M(age) = 29.76, SD = 11.25, 64.78% women) who completed the CBD. Results: We observed that none of the items presented differential functioning. A monofactorial structure was established. In this model a good fit was obtained by confirmatory factor analysis and a strict invariance by sex. The ordinal alpha was used to check the reliability and it fetched an index of .95. Conclusions: The Basic Depression Questionnaire has adequate psychometric properties. The absence of differential item functioning and the invariance by sex are guarantees of an adequate use to diagnose depression for men and women. So, its clinical use can help to differentiate between the specific diagnoses for depressive disorders and anxiety disorders.